2011
DOI: 10.1111/j.1365-2133.2011.10213.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of drug survival rates for adalimumab, etanercept and infliximab in patients with psoriasis vulgaris

Abstract: SummaryBackground Adherence to treatment is an indicator of treatment success. Long-term data on adherence to biologic treatment in psoriasis are lacking. Objectives To compare the tumour necrosis factor (TNF)-a inhibitors regarding drug survival rate and safety in patients with psoriasis. Methods This study is based on data from the Danish nationwide database DERM-BIO covering patients with psoriasis treated with a biologic agent. All patients who received anti-TNF-a treatment in academic referral centres wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
251
10
25

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(315 citation statements)
references
References 19 publications
29
251
10
25
Order By: Relevance
“…Successes achieved with currently available agents have raised the bar such that the goal for treatment is as low a state of disease activity as possible for all patients. Because conventional DMARD and biologic agents are not effective or tolerated in all patients, additional therapies are indicated 8,9,10,11,12,13 . Based on shorter-term data, apremilast showed the potential to offer patients with active PsA an additional treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Successes achieved with currently available agents have raised the bar such that the goal for treatment is as low a state of disease activity as possible for all patients. Because conventional DMARD and biologic agents are not effective or tolerated in all patients, additional therapies are indicated 8,9,10,11,12,13 . Based on shorter-term data, apremilast showed the potential to offer patients with active PsA an additional treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported data demonstrated that adalimumab, a biological drug, is an efficacious treatment for psoriatic arthritis and rheumatoid arthritis and is FDA approved for psoriasis. Adalimumab is a fully human monoclonal antibody IgG I against tumor necrosis factor alpha, which is able to interfere with the TNF-alpha activities (8)(9)(10). We sought to characterize the pattern of innate immune receptors in psoriatic skin of patients treated or not with adalimumab, in particular TLRI and TLR2, mostly involved in psoriasis, to clarify their role and to gain further insight into the potential role of such components for new therapeutic approaches.…”
Section: Fig 2 Immunohistochemical Staining Oftlr2 In a Healthy Patmentioning
confidence: 99%
“…One study compared drug survival rates for adalimumab, etanercept and infliximab in patients with psoriasis vulgaris. The drug survival rates were most favourable for infliximab, followed by adalimumab and etanercept [63].…”
Section: Discussionmentioning
confidence: 98%